Idebenone Delays Respiratory Decline in Duchenne Muscular Dystrophy - Parry, Nicola (MD Conference Express, 2015)
The randomized phase 3 DELOS trial was designed to evaluate idebenone, a synthetic quinone compound, in Duchenne muscular dystrophy. The data showed that idebenone was safe and well tolerated, and it significantly reduced loss of respiratory function in patients aged 10 to 18 years.